Determination of twenty herbicides in blood by ultrapressure liquid chromatography–tandem mass spectrometry. (October 2021) - Luo, Ruxin; Shen, Baohua; Xiang, Ping; Liu, Wei
Abstract: A sensitive and rapid method for the simultaneous determination of twenty herbicides (aclonifen, lactofen, terbutryn, butylate, carbetamide, fluazifop-P-butyl, propanil, prometryn, isoproturon, terbumeton, pretilachlor, pendimethalin, cycloxydim, tri-allate, metolachlor, diuron, alloxydim, prosulfuron, triflusulfuron-methyl, and acetochlor) in human blood is reported herein. Liquid-liquid extraction coupled with ultra-pressure liquid chromatography-tandem mass spectrometry was employed for the simultaneous analysis of all compounds in 15 min. Validation parameters were studied through the estimation of the limits of detection and quantification, calibration curves, sensitivity, spiked recovery and precision. The limits of detection ranged from 0.1 to 1.0 ng/mL. The limits of quantification ranged from 0.5 to 2.0 ng/mL. Good linearity was obtained for all compounds with R 2 > 0.99 in all cases. Furthermore, interday precision (< 15%) and intraday precision (< 15%) were shown to be satisfactory. Recoveries in spiked blood samples were evaluated, and acceptable values (88.0% 108.8%) were found. Finally, this method was successfully applied to the determination of fluazifop-P-butyl, isoproturon and acetochlor in blood samples from real forensic cases. These results suggest that this method is reliable for rapid forensic and clinical diagnosis. Highlights: A method for quantifying twenty herbicides in whole blood using UPLC–MS/MS was developed. The method has been designed to be suitable for rapid forensic and clinical diagnosis. Successfully applied in forensic routine analysis.